The incidence of the doctrine of own acts in the application of the CH 1980 to cases of international child abduction. Commentary to the SAP Oviedo of April 7, 2022 - Sánchez Cano, Mª Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The SAP Oviedo of April 7, 2022 dismisses an appeal filed by the father of a minor girl against the judgment issued by the Court of First Instance No. 7 of Oviedo, which decrees that the return of the minor daughter, who had been transferred by her mother to our country, from the United Kingdom is not appropriate. This, on the basis that the transfer of the child to Spain from the United Kingdom was consented to by her father, who was the one who filed the lawsuit and the subsequent appeal against the judgment issued in the first instance, which rejected his claims.
Keywords: child abduction; CH 1980; custody rights